THE HEAVY TOLL: ASSOCIATION OF MATERNAL OBESITY WITH FETOMATERNAL OUTCOMES– A CROSS-SECTIONAL STUDY IN KASHMIR - Dr. Sumaya Ramzan; Dr. Saima Wani; Dr. Rabia Khursheed; Dr. Diksha Dadlani (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Obesity, a chronic disease recognised by WHO, is rising globally and linked to adverse maternal and neonatal outcomes. In pregnancy, it increases the risk of gestational diabetes, hypertension, caesarean delivery, wound infections, and NICU admissions. Despite its growing impact, Indian data are limited. This study aims to assess and compare the impact of maternal BMI on GDM, PIH, and IHCOP, mode of delivery, intrapartum complications, and neonatal outcomes like birth weight, APGAR score, and NICU admission in a tertiary care centre in Kashmir. A cross-sectional comparative study was conducted over 18 months at SKIMS, Srinagar, including 224 gravid singleton women meeting the inclusion criteria. Data were analysed using SPSS Version 20.0. Obese women (Group A) had higher rates of GDM (37.5% vs. 11.1%, p<0.001), PIH (34.6% vs. 16.7%, p=0.003), and IHCOP (30.8% vs. 18.5%, p=0.038). LSCS was more frequent (77.9% vs. 54.6%, p<0.001), with macrosomia and failed induction exclusive to this group. Preterm birth (<35 weeks) occurred in 12.5% vs. 2.8% (p=0.002). Neonates of obese mothers had higher birth weights (p<0.001), lower APGAR scores (<7: 23.6% vs. 10.7%, p=0.021), and greater NICU admissions (25% vs. 11.1%, p=0.008). Wound infections (13.6% vs. 3.4%, p=0.041) and shoulder dystocia (5.8%, p=0.013) were also more frequent. No significant differences were found in eclampsia, abruptio placentae, PPH, or stillbirth. Thus, maternal obesity is strongly associated with pregnancy complications and adverse neonatal outcomes, stressing the importance of early weight management and tailored interventions in low-resource settings.